Synthesis of constructs for modeling consumers' understanding and perception of eco-labels - Taufique, Khan Md Raziuddin; Siwar, Chamhuri Bin; Talib, Basri Abdul Abdul; Sarah, Farah Hasan; Chamhuri, Norshamliza (© 2014 MDPI AG, 2018)
This article was published in the International Journal of Sustainability (Switzerland) [© 2014 by the author.] and the definite version is available at: https://doi.org/10.3390/su6042176 The Article's website is at: http://www.mdpi.com/2071-1050/6/4/2176